Wood-decaying polypores in the mountains of central Argentina in relation to Polylepis forest structure and altitude - Robledo, Gerardo Lucio (2010)
To determine how altitude and forest successional stage are related to richness and composition of wood-decaying polypore fungi in Polylepis mountain forests of central Argentina we sampled 48 forest plots of 900 m2 which included a range of successional stages and altitudes. We recorded a total of 19 species and our main results show that overall richness increased with forest successional stage and altitude, while endemic species richness was positively related only to altitude. Polypore community structure as exemplified by DCA Axes 1 and 2 was also related only to altitude with no pattern with forest successional stage, meaning polypore species are added during succession with no loss of early successional species. We conclude these forests must be managed to promote more mature forests and emphasis must be placed on a range of altitudes, especially highland areas where slow decomposition allows for a more diverse polypore community.